OBTAINING BIOCHAR FROM RICE HUSK AND STRAW - N. O. Appazov,; B. M. Bazarbayev,; T. Assylbekkyzy,; B. M. Diyarova,; S. A. Kanzhar,; S. Magauiya,; R. U. Zhapparbergenov,; N. I. Akylbekov,; B. A. Duisembekov, (Academic Scientific Journal of Chemistry, 2021)
This paper presents the results of research on obtaining biochar from agricultural plant waste such as rice husk and straw. The selection of the optimal conditions for thermolysis, such as the duration and temperature of the process, has been conducted. The thermolysis products are characterized for iodine adsorption activity, cumulative water pore volume, and for bulk density. The porous structure of the obtained products has been studied by scanning electron microscopy. Based on the results of the research conducted, it has been found that biochars obtained from husk and straw with a thermolysis duration of 30 minutes have low iodine sorption characteristics and water pore volumes. With an increase in the duration of thermolysis, the sorption characteristics improve, the optimal for the husk is the thermolysis duration of 60 minutes at a temperature of 500°C, and for straw, the optimal thermolysis duration is 60 minutes at a temperature of 300°C. The best option is biochar obtained from rice straw at a duration of 60 minutes and a thermolysis temperature of 300°C, having an iodine adsorption activity of 54.61%, a cumulative water pore volume of 0.941 cm3 /g and a bulk density of 169.29 g/dm3 . The obtained biochars from rice husk and straw have been studied by scanning electron microscopy at 4300 and 5000 times magnification, and they have a developed porous structure. According to the literature, it is known that biochar can also be used as a renewable energy source. Research has been carried out to determine the calorific value of the obtained biochars. To compare the calorific value of rice husk, straw and the obtained biochars, their heating values have been determined on a calorimeter. The highest heating value has a biochar obtained from husk at a duration of 60 minutes and at a thermolysis temperature of 400°C with a value of 17.520 kJ/g, the optimal for biochar obtained from straw is a duration of 60 minutes and a thermolysis temperature of 400°C with a value of 16.451 kJ/g. The experimental data obtained make it possible to use the obtained biochar from rice straw in the future as a biofertilizer to improve the characteristics of soils, as well as to use biochar obtained from rice husk to produce renewable fuel